Improving African livestock with reproductive technologies and genomics - International Livestock Research Institute (International Livestock Research Institute, 2011)
The promise of abundant milk and meat drives many poor African farmers to spend scarce money on imported cattle breeds. However, under the harsh conditions of Africa’s smallholder farms, these exotic breeds generally perform poorly. New breeding technologies promise to improve this situation, and generate a breeding pool of affordable, hardy and productive cattle breeds suitable for African farmers.